Basal Insulin Persistence, Associated Factors, and Outcomes After Treatment Initiation: A Retrospective Database Study Among People with Type 2 Diabetes Mellitus in Japan. Issue 1 (February 2017) - Hadjiyianni, Irene; Desai, Urvi; Suzuki, Shuichi; Ivanova, Jasmina; Cao, Dachuang; Kirson, Noam; Chida, Dai; Enloe, Caroline; Birnbaum, Howard; Perez-Nieves, Magaly
Abstract Introduction The objective of this study was to assess basal insulin persistence, associated factors, and economic outcomes for insulin-naïve people with type 2 diabetes mellitus (T2DM) in Japan. Methods People aged at least 18 years with T2DM with first claim for basal insulin between May 2006 and April 2013 (index date), no insulin use before index date, and continuous insurance coverage for 6 months before (baseline) and 12 months after index date were selected from the Japan Medical Center Database. On the basis of whether there were at least 30-day gaps in basal insulin treatment, patients were classified as continuers (no gap), interrupters (at least one prescription after gap), and discontinuers (no prescription after gap). A multinomial logistic regression model identified factors associated with persistence. Annual healthcare resource use and costs in the year after initiation were compared between continuers and interrupters and between continuers and discontinuers using propensity score-based inverse probability weighting to adjust for baseline differences. Results Of the 827 people included (mean age 50 years, ca. 71% male), 36% continued, 42% interrupted, and 22% discontinued basal insulin therapy in the year after initiation. Having at least one inpatient visit and using fewer classes of non-insulin antihyperglycemic medications during baseline were associated with lower likelihoods of continuing therapy. Relative to interrupters and discontinuers, continuers had lower hospitalization rates [continuers, 12.7%; interrupters, 25.4% (p < 0.001); discontinuers, 28.4% (p < 0.001)] and lower inpatient costs [continuers, ¥132, 013; interrupters, ¥225, 745 (p = 0.054); discontinuers, ¥320, 582 (p = 0.036)], but higher pharmacy costs [continuers, ¥158, 403; interrupters, ¥134, 301 (p = 0.039); discontinuers, ¥121, 593 (p = 0.002)] in the year after insulin initiation. Total healthcare costs were similar for the three cohorts. Conclusions Substantial proportions of people with T2DM in Japan interrupt or discontinue basal insulin within the year after initiation, and they have higher rates and costs of hospitalizations than patients who continue with their insulin therapy. Further research is needed to understand reasons behind basal insulin persistence and the implications thereof to help clinicians manage T2DM more effectively. Funding Eli Lilly and Company, Boehringer Ingelheim.